PENERAPAN SANKSI PIDANA MATI KEPADA KORUPTOR SUATU PERBANDINGAN HUKUM ANTARA INDONESIA DAN CINA - Steven Makaruku (SASI, 2016)
Under the provisions of Law No. 31 Year 1999 jo Law No. 20 of 2001, the type of criminalsanctions can be imposed judges against the accused of corruption that is for people whocommit criminal acts of corruption in Indonesia is Criminal Dead, Criminal Prison and PenalSupplement. Sanctions death penalty to corrupt when corruption was carried out on fundingearmarked for coping with the hazards, national disasters, social unrest is widespread, theeconomic and monetary crisis management, and the repetition of acts of corruption. Underthe provisions of this Article, the application of sanctions the death penalty for corruptionimposed only if it is done in certain circumstances. In contrast to China, the Chinese government's commitment to eradicate corruption no doubt, not just a slogan or a rhetorical,because in the system of prevention of corruption in China when an officer was proved onlyaccept bribes, then legal sanction given to him to till the death penalty. related to theimplementation of sanctions Criminal die for actors in Indonesia and China, it is seen thatpolitical action imposition of capital punishment against perpetrators of corruption inIndonesia is still weak, while in China's political action imposition of capital punishmentagainst the perpetrators of the crime of corruption is very strong due to the strongcommitment of government to combating corruption. A strong commitment to prevent andcombat corruption could prove the decrease of corruption